Beyond human intentions and emotions - Juan, Elsa; Frum, Chris; Bianchi-Demicheli, Francesco; Yi-wen, Wang; Lewis, James W.; Cacioppo, Stephanie (Frontiers in Human Neuroscience, 2013)
Although significant advances have been made in our understanding of the neural basis of action observation and intention understanding in the last few decades by studies demonstrating the involvement of a specific brain network (action observation network; AON), these have been largely based on experimental studies in which people have been considered as strictly isolated entities. However, we, as social species, spend much more of our time performing actions interacting with others. Research shows that a person’s position along the continuum of perceived social isolation/ bonding to others is associated with a variety of physical and mental health effects. Thus, there is a crucial need to better understand the neural basis of intention understanding performed in an interpersonal and emotional context. To address this issue, we performed a meta-analysis using of fMRI studies over the past decade that examined brain and cortical network processing associated with understanding the intention of others actions versus those associated with passionate love for others. Both overlapping and distinct cortical and subcortical regions were identified for intention and love, respectively. These findings provide scientists and clinicians with a set of brain regions that can be targeted for future neuroscientific studies on intention understanding, and help further develop neurocognitive models of pair-bonding.